Dual Function of Chip Calls Depending on Changing Call Rate Related to Risk Level in Territorial Pairs of White-Eared Ground-Sparrows - Méndez Vázquez, Carolina (2017)
Different mechanisms have been proposed for encoding information into vocalizations: variation of frequency or temporal characteristics, variation in the rate of vocalization production, and use of different vocalization types. We analyze the effect of rate variation on the dual function of chip calls (contact and alarm) produced by White‐eared Ground‐sparrows (Melozone leucotis). We conducted an acoustic playback experiment where we played back 1 min of four chip call rates (12, 36, 60, 84 calls/min). We measured the response of territorial pairs using behavioral responses, and fine structural features of calls produced in response to those playbacks. White‐eared Ground‐sparrows showed more intense behavioral responses to higher than lower call rate playbacks. Both individuals of the pair approached the source of the playback stimulus faster, produced the first vocalization faster, produced more vocalizations, and spent more time close to the stimulus in higher call rate than in lower call rate playbacks. Frequency and duration characteristics of calls (chip and tseet) were similar in response to all call rate playbacks. Our playback experiment elicited different intensity of behavioral responses, suggesting that risk‐based information is encoded in call rate. Our results suggest that variation in the rate of chip call production serves a dual function in this species; calls are used at lower rates for pair contact and at higher rates for alarm/mobbing signals.